2016
DOI: 10.3389/fncel.2016.00057
|View full text |Cite
|
Sign up to set email alerts
|

KIF5C S176 Phosphorylation Regulates Microtubule Binding and Transport Efficiency in Mammalian Neurons

Abstract: Increased phosphorylation of the KIF5 anterograde motor is associated with impaired axonal transport and neurodegeneration, but paradoxically also with normal transport, though the details are not fully defined. JNK phosphorylates KIF5C on S176 in the motor domain; a site that we show is phosphorylated in brain. Microtubule pelleting assays demonstrate that phosphomimetic KIF5C(1-560)S176D associates weakly with microtubules compared to KIF5C(1-560)WT. Consistent with this, 50% of KIF5C(1-560)S176D shows diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Since the spatial relationship between mitochondria and microtubules is not affected by H 2 O 2 (Fig 2G), we reasoned that the activity of one of these 2 components could be the target of p38 for achieving ROS-induced inhibition of motility. Kinesin KIF5C has been already described as target of p38 (Morfini et al, 2013): phosphorylation of its serine residue in position 176 regulates cargo transport by promoting disengagement of the motor from microtubule tracks (Padzik et al, 2016). Kif5B, one of the kinesin responsible for movements of mitochondria (Tanaka et al, 1998) together with Kif1B and KLP (Nangaku et al, 1994; Tanaka et al, 2011), belongs to the same kinesin family as Kif5C (Kanai et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Since the spatial relationship between mitochondria and microtubules is not affected by H 2 O 2 (Fig 2G), we reasoned that the activity of one of these 2 components could be the target of p38 for achieving ROS-induced inhibition of motility. Kinesin KIF5C has been already described as target of p38 (Morfini et al, 2013): phosphorylation of its serine residue in position 176 regulates cargo transport by promoting disengagement of the motor from microtubule tracks (Padzik et al, 2016). Kif5B, one of the kinesin responsible for movements of mitochondria (Tanaka et al, 1998) together with Kif1B and KLP (Nangaku et al, 1994; Tanaka et al, 2011), belongs to the same kinesin family as Kif5C (Kanai et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, all in all, the molecular spectrum of KIF5C related disorders appears to be narrow with a recurrent mutation affecting amino acid Glu237, and with all mutations clustered within the microtubule binding domain of the protein. Mutations of KIF5C have been shown to cause Kinesin proteins to lose their ability to hydrolyze ATP and lead to a non‐functional motor domain (Padzik et al, ). Mutations of the amino acid Glu237 have been shown to affect the binding ability of these microtubule proteins to their targets, protein folding and ATP hydrolysis (Cavallin et al, ; Poirier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Initial single molecule TIRF microscopy observations revealed that KIF1A possesses the novel ability to undergo extensive pausing during a run on taxol-stabilized microtubules ( Figure 1A, Movie S1). While other kinesin motors have been shown to exhibit transient pauses [27,28], the high pause frequency ( Figure 2E, Table 1) of KIF1A has not been previously characterized, compelling us to investigate this behavior further. Additionally, the discovery of this novel pausing behavior led us to redefine our nomenclature of KIF1A motility by dissecting KIF1A motility into three segments ( Figure 1A).…”
Section: Kif1a Exhibits Pausing Behavior and Superprocessive Motilitymentioning
confidence: 96%